2020
DOI: 10.1136/bmjopen-2019-034926
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the management and costs of headache disorders in Spain during the period 2011–2016: a retrospective multicentre observational study

Abstract: ObjectivesTo investigate the number and characteristics of the Spanish population affected by headache disorders and the direct medical cost that these patients represent for the healthcare system.DesignA retrospective multicentre observational study.SettingRecords from all patients admitted with headache in primary and secondary care centres in Spain between 2011 and 2016 that were registered in a Spanish claims database were included in the analysis. Direct medical costs were calculated using the standardise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
3
1
0
2
Order By: Relevance
“…Our study findings indicate a high and increasing number of patients with physician-diagnosed migraine, consistent with published literature [ 7 , 36 ]. However, our reported prevalence of physician-diagnosed migraine (5.5% of all age population and 6.5% of people aged > 18 years old) is lower than prevalence estimates published for Spain, potentially due to differences in methodologies [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study findings indicate a high and increasing number of patients with physician-diagnosed migraine, consistent with published literature [ 7 , 36 ]. However, our reported prevalence of physician-diagnosed migraine (5.5% of all age population and 6.5% of people aged > 18 years old) is lower than prevalence estimates published for Spain, potentially due to differences in methodologies [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…As expected, most migraine patients in our study were women of working age with several comorbidities [ 7 , 37 , 39 ]. The most frequently observed comorbidities were coexisting chronic pain (50.8%), metabolic (38.6%), neuropsychiatric (35%), digestive (25.4%), and cardiovascular (25.4%) conditions.…”
Section: Discussionsupporting
confidence: 66%
“…The direct costs represented 32.0% of the total burden (344 million euros), 39.2% being for primary care visits, 28.7% for specialist visits, 20.5% for emergency room visits and a further 11.7% for migraine-specific prescription drugs. Similar results have been reported by Darbà and Marsà [ 21 ] in a recent study based on data from 2011 to 2016. These authors also found that headache disorders summed a total annual cost of 10,716,086 euros and migraine alone represented 7,302,718 euros of the total annual cost.…”
Section: Introductionsupporting
confidence: 92%
“…De acuerdo con un estudio recientemente publicado, en Europa estima una prevalencia global anual de un 38% de la población 2 , aumentando esta tasa de prevalencia hasta el 79% si consideramos cualquier tipo de dolor de cabeza 2 . Además, las tasas de prevalencia de ambos tipos de dolor de cabeza, se han duplicado desde 2011 3 . Casi todas las personas experimentan o experimentarán un dolor de cabeza en algún momento de sus vidas 4 .…”
Section: Introductionunclassified
“…Casi todas las personas experimentan o experimentarán un dolor de cabeza en algún momento de sus vidas 4 . En España, según un estudio con datos retrospectivos los costes médicos directos atribuibles al dolor de cabeza (de los cuales la migraña fue responsable del 50% de las hospitalizaciones, y el TTH de 14,47%) ascendieron a más de 10 millones de € anuales 3 . Las mujeres se ven más afectadas por este tipo de dolor de cabeza que los hombres, tanto en atención primaria (un 71,9% de mujeres), como hospitalaria (69,6%) 3 .…”
Section: Introductionunclassified